2018
DOI: 10.1148/radiol.2017170213
|View full text |Cite
|
Sign up to set email alerts
|

Subacute and Chronic Left Ventricular Myocardial Scar: Accuracy of Texture Analysis on Nonenhanced Cine MR Images

Abstract: Purpose To test whether texture analysis (TA) allows for the diagnosis of subacute and chronic myocardial infarction (MI) on noncontrast material-enhanced cine cardiac magnetic resonance (MR) images. Materials and Methods In this retrospective, institutional review board-approved study, 120 patients who underwent cardiac MR imaging and showed large transmural (volume of enhancement on late gadolinium enhancement [LGE] images >20%, n = 72) or small (enhanced volume 20%, n = 48) subacute or chronic ischemic sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 33 publications
2
125
0
1
Order By: Relevance
“…Technical University of Lodz, Lodz, Poland) (21) as previously described (15,22). T1 and T2 maps (midventricular short axis and horizontal long axis) were exported as single Digital Imaging and Communications in Medicine images for further analysis, and regions of interest encompassing the entire left ventriclar myocardium were drawn by an experienced observer (B.B.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical University of Lodz, Lodz, Poland) (21) as previously described (15,22). T1 and T2 maps (midventricular short axis and horizontal long axis) were exported as single Digital Imaging and Communications in Medicine images for further analysis, and regions of interest encompassing the entire left ventriclar myocardium were drawn by an experienced observer (B.B.)…”
Section: Methodsmentioning
confidence: 99%
“…TA also detects tissue changes that remain imperceptible to the human eye (14) by quantifying gray-level patterns and pixel interrelationships in an image (14). Recently, applications of TA in cardiac MRI have been described in the setting of myocardial infarction, demonstrating the potential of TA for detecting small myocardial scars at cine imaging (15) and for differentiating acute versus chronic myocardial infarction (16).…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Most recently, several commercial vendors have begun to take an interest in this technology and to integrate these algorithms into their software. [50][51][52] Outside of cardiac segmentation on MRI, algorithms have also been developed to detect subacute or chronic myocardial scar 28 and to predict patient survival and mechanisms of right heart failure in pulmonary hypertension. 29 Machine learning techniques have also been applied to characterizing cardiac disease on echocardiography (ECHO).…”
Section: Applications To Cardiovascular Diseasementioning
confidence: 99%
“…Texture analysis was also used to create probability maps using LGE images that aid the visual inspection of the myocardial tissue . Recently, it was reported that texture analysis of nonenhanced cine MRI can differentiate between different etiologies of left ventricular hypertrophy, between acute and chronic myocardial infarction, and between controls and patients with subacute and chronic myocardial infarction …”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, it was reported that texture analysis of nonenhanced cine MRI can differentiate between different etiologies of left ventricular hypertrophy, 11 between acute and chronic myocardial infarction, 12 and between controls and patients with subacute and chronic myocardial infarction. 13 Histological properties of scarred myocardium differ from normal myocardium and in consequence, textural properties should also be different. The fibrosis formation causes distortion of the normal myocardium architecture thus altering the texture properties.…”
Section: Introductionmentioning
confidence: 99%